(3eMGSHI GdTQcGJs - (3eYJR Cejf(B, (3GdSYjOs ((3YeGf(B;(3ecJHI GdeLJeY GdYQHj(B:s (3OGQ GdGYUGQ GdYdej(B,s, 2012)
(3TQcGJ GdCehGd Ch TQcI GdeSGgeI, GdGfOeGL Ch GdSjWQI Hjf GdTQcGJ, EYOGO bGFeI GdeQcR GdeGdj GdehMOI aj JGQjN dGMb dJGQjN GdTQGA, GdYedjGJ GdeJHGOdI Hjf GdTQjcJjf GdbGHVI h GdJGHYI, YedjGJ GdGbQGV Hjf TQcI GdeLehYI GdGbJUGOjI ef NdGd EUOGQ GdSfOGJ, GdeMGSHI Yf GdYedGJ GdCLfHjI, YbhO GdUQa GdBLdI, GdbhGFe GdeGdjI GdeLeYI Ch GdehMOI Yf GdaQhY Ch GdTQcGJ GdJGHYI GdCLfHjI, GdefMGSHI Yf YbhO GdGjLGQ WhjdI GdCLd h GdeMGSHI Yf GdGdJRGeGJ WhjdI GdCLds
Keywords: (3GdTQcGJ GdCLfHjIs; (3GdTQcGJ(B- (3eMGSHIs; (3TQcGJ GdeSGgeIs